The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/ijbm-02-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Islamic banking adoption in Tunisia: empirical analysis

Abstract: Purpose The purpose of this paper is to identify the main factors influencing the adoption of Islamic banking services in Tunisia. Design/methodology/approach The paper presents primary data collected by self-administered questionnaires involving a sample of 239 respondents located in Tunis city. Respondents were conventional banks’ customers who were actually non-users of Islamic banking. A descriptive statistical analysis was conducted to determine consumers’ awareness of Islamic banking. Findings The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
95
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(131 citation statements)
references
References 53 publications
17
95
1
1
Order By: Relevance
“…The findings from our present review also support these conclusions. For example, most studies in the Muslim majority countries have focused only on the issue of efficiency of the Islamic finance system and customer satisfaction (e.g., Moktar et al 2006;Sufian 2010;Kaabachi and Obeid 2016;Ltifi et al 2016;Chazi et al 2018;Hussein 2010;Butt et al 2018;Estiri et al 2011). We have identified numerous critically important yet unexplored opportunities to integrate insights from the global Islamic finance literature with a focus on Muslim majority countries.…”
Section: Research Questions Related To Other Issuesmentioning
confidence: 99%
“…The findings from our present review also support these conclusions. For example, most studies in the Muslim majority countries have focused only on the issue of efficiency of the Islamic finance system and customer satisfaction (e.g., Moktar et al 2006;Sufian 2010;Kaabachi and Obeid 2016;Ltifi et al 2016;Chazi et al 2018;Hussein 2010;Butt et al 2018;Estiri et al 2011). We have identified numerous critically important yet unexplored opportunities to integrate insights from the global Islamic finance literature with a focus on Muslim majority countries.…”
Section: Research Questions Related To Other Issuesmentioning
confidence: 99%
“…This is following the research of Wahab (2013) declared religion is the dominant factor that affects the intention to become the Bank's customers. Research (Newaz et al 2016;Kaabachi, et al 2016) states that Religiosity affects consumer intention. From the study of the theory above is made hypothesis:…”
Section: Religiosity Towards Consumer Intentionmentioning
confidence: 99%
“…In the banks created a positive brand, attitude can increase the consumer's intention to use banking services. Some research(Kaabachi et al 2016;Molinillo et al 2018; and Lee and Lee, 2018) stated that the company's image affects consumer intention . From the study of the theory above is made hypothesis:…”
mentioning
confidence: 99%
“…Indeed, it was found that a consumer who was better knowledgeable about Islamic banking products has had greater intention to use them. Kaabachi and Obaid (2016) inspected the influence of customers' perception and willingness to adopt Islamic banking in Tunisia by testing the diffusion innovation theory of Rogers (2003). The study surveyed the customers of conventional banks located in Tunis City and found that bank reputation, the relative advantage of Islamic banks and compatibility with religious beliefs influence positively the intention to use it.…”
Section: Previous Researchmentioning
confidence: 99%